Revolutionising Higher Education The Significance of Micro Credentials in Malaysias Hybrid Learning Environment A Success Story from UMPSA - Awanis, Romli (UMPSA, 2023)
The higher education landscape in Malaysia has undergone rapid transformation in recent years, driven by technological advancements and evolving workforce needs. To keep up with global educational trends, the Malaysian government has incorporated the concept of globalised online learning into its national agenda, as outlined in the Malaysia Education Blueprint 2015-2025.